Improving Teachers’ Classroom Practices Using Social Network Based Collaborative Tools as an Alternative to Traditional Face-to-Face Collaboration Strategies: The Case of M’sila Secondary School EFL Teachers - Bouguerra, Amel; Kara Mustefa-Boussena, Leila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
The profuseness of social network based collaborative tools manifested mainly in social platforms such as; Facebook groups, what’s up, e-mail, and online chats, provide opportunities for English as foreign language teachers to collaborate virtually with peers and educators. Accordingly, they construct new teaching knowledge, exchange related documents, and elaborate new strategies to improve their classroom practices. Subsequently, they overcome the limits encountered in traditional face-to-face collaborative strategies. Therefore, the study aims to explore face-to-face collaboration limitations as well as the impact of informally incorporating social network collaborative tools on improving teacher's classroom practices. Besides, the study aspires to investigate their role in enhancing teachers’ collegial partnership. The research opted for a qualitative method wherein online semi-structured interview with open-ended questions was conducted with fifteen (15) EFL teachers from different secondary schools in M'sila, Algeria. The findings emphasised the positive role of social network based collaborative tools in improving EFL teachers' classroom activities, overcoming the obstacles of traditional face-to-face collaboration, and raising partnership. Nevertheless, a blended collaboration is recommended to balance between teachers’ collaborative styles. In addition, we recommend more research to corroborate or nullify their effectiveness for a formal integration into the educational realm.